Phytoremediation of heavy metal on entisols and plant uptake amended with palm oil mill effluent (POME) sludge - Khairuddin, Mohd Nizar; Md Isa, Isharudin; Wan Abdul Rahman, Wan Mohd Nazri; Ariffin, Mohd Rizal; Syahlan, Syahrizan; Abd Karim, Khairul Najmuddin; Mohamad, Azham (Penerbit Universiti Malaysia Perlis, 2023)
Palm oil mill effluent (POME) sludge was derived from about 50% of wastewater effluent of fresh fruit bunch (FFB) productions. The objective of this study is to determine the effect of contaminant status which was applied with POME sludge on Entisols and plant uptake of maize growth. POME sludge obtained from the Jengka 8 FELDA Palm Oil was used in this study. The maize (Zea mays) was used as a test crop and planted in Rasau series soil (Entisols). The soil, leaves and stem samples were air-dried, homogenized and sieved. Heavy metal analysis identified the existence of Cu, Cr, Cd, Zn, Pb, Ni and Mn elements by the sequential extraction procedure using optical emission spectrometry (ICP-OES). The physicochemical of POME sludge showed that most heavy metals in each treatment fulfilled the WHO/FAO standard and were safe for human consumption. After applying treatments on Entisols, a small amount of Cu, Cr, Zn, Pb, Ni and Mn was retrieved from the exchanges phase. Small amount of Cr, Ni and Mn were identified in the stems and leaves. Zn, Cd, Pb and Cr were not detected in the bioavailable forms, while Cu was only available in the mixing ponds sludge samples. The results showed that most heavy metal properties contained low residual fractions from the soil and plant uptake in stems and leaves. The application of POME sludge in agricultural practices might offer a sustainable utilization of waste materials in the oil palm plantation.